Annual Address to the Board of Directors, September 30, 1963 - Woods, George D. (World Bank, Washington, DC, 2019)
George D. Woods, President of the World Bank Group, discussed the following: the willingness of the capital-exporting countries to continue and increase their annual contributions in support of the International Development Association (IDA); the operations of the International Finance Corporation (IFC); and the growing activity of the Bank Group, under the leadership of IFC, in the establishment and support of local private industrial finance companies. He addressed three problems that put a brake on economic progress: the commodity problem, the debt problem, and the policy problem. He sought expansion of Bank support to agriculture, industry, and education.